A Cross-Sectional Investigation Of Interlingual & Intralingual Errors Made By EFL Arab Jordanian University Students In The Use Of Prepositions In Their Writing - Qasem Tahaineh, Yousef Sharif (2009)
The present study was a cross-sectional investigation into Arab Jordanian first-, second- and third-year universtiy EFL students’ errors in the use of prepositions in written language production. Kajian ini berhubung dengan penyiasatan rentas-silang tentang kesilapan penggunaan kata depan / preposisi dalam penulisan, dalam kalangan pelajar Arab EFL tahun satu, dua dan tiga di universiti-universiti di Jordan.